Variable Volumetric Stiffness Fluid Mount Design. (2004) - Vahdati, Nader; Ahmadian, Mehdi
Abstract : Passive fluid mounts are commonly used in the automotive and aerospace applications to isolate the cabin from the engine noise and vibration. Due to manufacturing and material variabilities, no two identical fluid mount designs act the same. So, fluid mounts are tuned one by one before it is shipped out to customers. In some cases, for a batch of fluid mounts manufactured at the same time, one is tuned and the rest is set to the same settings. In some cases they are shipped as is with its notch frequency not being in its most optimum location. Since none of the passive fluid mount parameters are controllable, the only way to tune the mount is to redesign the mount by changing fluid, changing inertia track length or diameter, or changing rubber stiffness. This trial and error manufacturing process is very costly. To reduce the fluid mount notch frequency tuning cycle time, a new fluid mount design is proposed. In this new fluid mount design, the notch frequency can be easily modified without the need for any redesigns. In this paper, the new design concept, and its mathematical model and simulation results will be presented.